EDUKASI DAN PELATIHAN PENGOLAHAN MINUMAN IMUNOMODULATOR PADA PENDERITA TB PARU DI WILAYAH PUSKESMAS CEMPAKA BANJARBARU - Ratih Dewi Dwiyanti; Nurlailah Nurlailah; Aima Insana (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2026)
Pulmonary TB is still a disease that is often found in the Cempaka Banjarbaru Community Health Center. Based on data from the Cempaka Health Center for January - December 2022, there are 36 tuberculosis sufferers who are still actively seeking treatment. Treatment of pulmonary TB with anti-tuberculosis drugs (OAT) takes several months so it is prone to causing side effects in sufferers. To minimize the side effects of using OAT while increasing the patient's immune system, it is necessary to consume natural ingredients (moringa, meniran and ginger) which have minimal side effects and act as immunomodulators. The aim of the activity is to increase participants' knowledge about tuberculosis and how it is transmitted as well as how to use herbal plants as immunomodulators to minimize side effects due to the use of OAT. The method used in this activity is filling out a questionnaire sheet (pretest) followed by a presentation of the material. Before the posttest was carried out, the participants were given training on how to process herbal drinks from 3 herbal ingredients, namely Moringa leaves, meniran and ginger (Kemeja) which were made in powder form for 2 hours and continued with filling out a questionnaire sheet (posttest). The results of community service can be seen based on the questionnaire sheet which shows an increase in participants' knowledge about pulmonary TB disease by 10% and behavior in preventing pulmonary TB by 10% and participants were able to make immunomodulatory drinks in the form of powder such as Kemeja (moringa, meniran, ginger). Based on the results of evaluation and monitoring, sufferers stated that their appetite increased after drinking SHIRT tea powder. It is hoped that the increase in appetite can increase the sufferer's immune system so that they can suppress the side effects of the OAT drugs they consume.